2014
DOI: 10.1039/c4ta01373e
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal cubes for the enhanced degradation of organic dyes

Abstract: The shape of cubic silica colloids is exploited to form close-packed structures, whereas the hollow core of the cubes may host functional substances. A proof-of-principle of this approach is presented for iron oxide particles (hematite, a-Fe 2 O 3 ) confined inside silica cubes that display the ability to accelerate the degradation of the organic dyes methylene blue and rhodamine B in the presence of hydrogen peroxide (modified Fenton reaction). The silica coating does not impede the reaction, since degradatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…A third and most intriguing dewetting mechanism is offered by a modified photo-Fenton reaction 21 , which takes advantage of the photocatalytic properties of the colloidal substrate to degrade the silane hydrophobe layer. While this mechanism only works with photo-active substrates, we found it particularly interesting as the particles can remain in their native aqueous medium at a neutral pH and be dewetted by simply exposing them to light.…”
Section: Resultsmentioning
confidence: 99%
“…A third and most intriguing dewetting mechanism is offered by a modified photo-Fenton reaction 21 , which takes advantage of the photocatalytic properties of the colloidal substrate to degrade the silane hydrophobe layer. While this mechanism only works with photo-active substrates, we found it particularly interesting as the particles can remain in their native aqueous medium at a neutral pH and be dewetted by simply exposing them to light.…”
Section: Resultsmentioning
confidence: 99%
“…The Fe 2 O 3 @DTT also showed a stronger ability to purify the wastewater in contrast with other reported Fenton catalysts (Table 4, ref. [38][39][40][41][42][43][44][45][46][47][48][49]. This encouraging result can be explained by the high dispersion of iron oxide.…”
Section: Examination Of the Catalytic Performance Of The Fenton Reactionmentioning
confidence: 99%
“…A more extended study of colloidal cubes was performed by Castillo et al 24 Their study included hematite cubes and cubes stabilized by a protecting polymer later. Subsequently, Castillo et al 25 demonstrated that silica cubes containing hematite could enhance the degradation of organic dyes. A review on the self-assembly of colloids possessing novel shapes has been written by Sacanna et al 26 Moreover, experimentally Wetterskog et al 21 found the appearance of porous bundles of cubes under a weak external field and more compact ones under a stronger external field.…”
Section: Introductionmentioning
confidence: 99%